Impact of nitrogen availability upon the electron requirement for carbon fixation in Australian coastal phytoplankton communities. (25th April 2018) - Hughes, David J.; Varkey, Deepa; Doblin, Martina A.; Ingleton, Tim; Mcinnes, Allison; Ralph, Peter J.; van Dongen‐Vogels, Virginie; Suggett, David J.
Abstract: Nitrogen (N) availability affects phytoplankton photosynthetic performance and regulates marine primary production (MPP) across the global coast and oceans. Bio‐optical tools including Fast Repetition Rate fluorometry (FRRf) are particularly well suited to examine MPP variability in coastal regions subjected to dynamic spatio‐temporal fluctuations in nutrient availability. FRRf determines photosynthesis as an electron transport rate through Photosystem II (ETRPSII ), requiring knowledge of an additional parameter, the electron requirement for carbon fixation ( KC ), to retrieve rates of CO2 ‐fixation. KC strongly depends upon environmental conditions regulating photosynthesis, yet the importance of N‐availability to this parameter has not been examined. Here, we use nutrient bioassays to isolate how N (relative to other macronutrients P, Si) regulates KC of phytoplankton communities from the Australian coast during summer, when N‐availability is often highly variable. KC consistently responded to N‐amendment, exhibiting up to a threefold reduction and hence an apparent increase in the efficiency with which electrons were used to drive C‐fixation. However, the process driving this consistent reduction was dependent upon initial conditions. When diatoms dominated assemblages and N was undetectable (e.g., post bloom), KC decreased predominantly via a physiological adjustment of the existing community to N‐amendment. Conversely, for mixed assemblages, N‐addition achieved a similar reduction in KC through a change in community structure toward diatom domination. We generate new understanding and parameterization of K C that is particularly critical to advance how FRRf can be applied to examine C‐uptake throughout the global ocean where nitrogen availability is highly variable and thus frequently limits primary productivity.